FOREIGN EXPERIENCE OF THE FINANCING OF HIGHER EDUCATION INSTITUTIONS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The fact that there is a high demand for higher education in Uzbekistan, the implementation of reforms in all processes related to the continuous development of the financing system and structure of higher education institutions remains one of the important issues. In this article, while providing financial independence to higher education institutions, they have to deal with complex tasks such as financial stability, inclusiveness and quality of education.